(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
During the growing season of 2023, this study was conducted inside the wooden canopy of one of the private nurseries in Kirkuk, Iraq, to investigate the effect of leaf spraying with gibberellic acid GA3 at three concentrations (0, 50, 100) mg L-l and salicylic acid at the same three concentrations (0, 50, 100) mg L-l on some growth traits as well as the mineral content of Aswad Diala type fig seedlings. Three repeat tests were conducted out as a factorial experiment utilizing five seedlings for each experimental unit, using a randomized complete block design (R.C.B.D.).. The results obtained indicated that leaf spraying with gibberellic acid at a concentration of 100 mg L-l led to a significant increase in their chemical content of the total chlorophyll, and the percentage of nitrogen in the leaves. Such spraying also increased most of the vegetative growth traits of the fig seedlings, the length and diameter of the main stem, number of branched leaves, and leaf index. Spraying gibberellic acid at the concentration 50 mg L-l led to a significant increase in leaf areas, and the percentage of phosphorous and potassium in the leaves. Salicylic acid is sprayed at a dosage of 100 mg L-l resulted in a significant rise in the majority of the qualities evaluated (the rate of increase in the length and diameter of the main stem, number of branched leaves, total chlorophyll index, and the percentage of macronutrients in leaves NPK). The combined interaction between the sprayed gibberellic and salicylic acids had a significant effect as well.